OCCURRENCE OF RASTRELLIGER FAUGHNI MATSUI IN THE INDIAN WATERS - Gnanamuthu, J C (Indian Journal of Fisheries, 2011)
This is the first record of the mackerel, Rastrelliger faughni from the Indian ocean. The characters that clearly distinguish this species from others of Rastrelliger are the few and short gill rakers, more slender body, shorter head, maxillary and mandible.